Pengungkapan Diri dalam Perseteruan Youtuber Kembar Tasya Farasya dan Tasyi Athasyia - Putri Widya Sari (Unitri Press, 2023)
Communication Privacy Management (CPM) theory is a theory that addresses the tension between openness and privacy, between